GDP Movements in High and Moderate HDI Economies: An Empirical Investigation - Verma, N. M. P.; Gaur, Monika; Kant, Ravi (Archives of Business Research, 2020)
Economists worldwide acknowledge the estimation and implications of Gross Domestic Product (GDP) and Human Development Index (HDI) as a measure of development across the globe. The analysis of GDP and its various components are still useful in order to observe the financial scenario of the economy. Since GDP does not include the various relevant components of socio-economic and environmental activities, it also does not reveal the real picture of economic progress. Several efforts have been made by economists worldwide to quantify better indicators of wellbeing. The Human Development Report, 1996, pioneered the casual relationship between economic growth and human development. There is a usual relationship between these two, because economic growth creates the basis for human development via providing financial benefits or monetary gains to the economy, provided that the formulation of rational policies and their implementation are appropriately executed. This study tries to synthesize economic growth and human development. The research employs Spearman rank correlation and Logistic regression of high and middle human development countries across 1990 to 2017, to determine the association mentioned above. The data is from the UNDP database and various reports and articles related to human development and economic growth.Policy implication is useful.